Study Of Signal Quality Relationship On The Number Of Clusters And Propagation Parameters In Mobile Comumunication - Injilia Pebrina Sari (IHSA Institute, 2020)
A suitable telecommunications system to support a mobile communication system is a wireless communication system, which is a radio communication system complete with transmitting antennas and radio equipment. To be able to cover such a wide coverage, the coverage area is divided into sub-areas called cells. A collection of several cells is called a cluster, and several clusters will form a mobile cellular communication network area. The number of clusters in an area is affected by changes in parameters, especially the pathloss from the propagation environment. Planning in designing a communication network is needed to be able to see how much influence the parameter changes, especially the propagation attenuation factor and the number of clusters, is to make a computer program for cell planning. From the cell planning program, it can be obtained that the value of c/i is influenced by changes in the value of J when the value of n is 3.9. The value of c/i when the value of J is 3 is 6.5321. The value of c/i when the value of J is 4 is 8.4062. The value of c/i when the value of J is 5 is 9.8599. The value of c/i when the value of J is 6 is 11.0476. The value of c/i when the value of J is 7 is 12.0518. The value of c/i when the value of J is 8 is 12.9217. The value of c/i when the value of J is 9 is 13.6889. The value of c/i is influenced by changes in the value of n when the value of J is 15. The value of c/i when the value of n is 3 is 17.0167. The value of c/i when the value of n is 3.2 is 18.6698. The value of c/i when the value of n is 3.4 is 20.3231. The value of c/i when the value of n is 3.6 is 21.9761. The value of c/i when the value of n is 3.8 is 23.6293. The value of c/i when the value of n is 3.9 is 24.4561. The greater the number of cells, the greater the value of the signal ratio ratio (c/i) in the propagation. The propagation attenuation value is directly proportional to the signal ratio ratio (c/i). The greater the number of cells and the propagation attenuation, the greater the signal ratio ratio (c/i). The greater the value of the signal ratio ratio (c/i), the better the received signal quality.